Pengaruh Pengenaan Sanksi Administrasi dan Kesadaran Wajib Pajak terhadap Tingkat Kepatuhan Wajib Pajak Kendaraan Bermotor di Provinsi Sumatera Utara - Reza Hanafi Lubis (Al-Buhuts, 2023)
The purpose of this study aims to determine the effect of imposition of administrative sanctions, awareness of taxpayers and application of the e-Samsat system on partial and simultaneous motor vehicle taxpayer compliance in the South Medan Samsat. This research is a Quantitative Research using Primary Data. This study used a sample of 100 taxpayer respondents using accidental sampling technique. The data analysis technique used in this study uses validity test, reliability test, normality test, multiple linear regression test, and hypothesis test (F test and T test). The data was processed using SPSS Version 23. The results showed that partially Tax Administration Sanctions (X1) and Taxpayer Awareness (X2) were accepted, which means they have an effect on Motor Vehicle Taxpayer Compliance in North Sumatra Province, while the Implementation of the E-Samsat Program is rejected, which means it has no effect on Taxpayer Compliance. As for Simultaneously Tax Administration Sanctions (X1), Taxpayer Awareness (X2), Implementation of E-Samsat (X3) have a significant effect on Motor Vehicle Taxpayer Compliance in the South Medan Samsat.